Etiology of Spastic Diplegia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The clinical and etiologic profile of spastic diplegia was studied in a retrospective chart review of 54 patients diagnosed during a 12-year period at Montreal Children's Hospital, Quebec, Canada.